(untitled) (City: History, Culture, Society, 2021)
Chokolivka is a unique part of Kyiv urban space. In the second half of the 60s it underwent transformation as a result of which it turned from rustical outskirts into a progressive part of Kyiv. Due to massive construction of residential buildings the first housing estate in the Ukrainian SSR was established. Finally, Chokolivka lived up to the “Soviet dream” in the external and internal imaginations. For external spectators, embodied by American journalists, a touristic route through the rayon was established, whereas Soviet citizens sincerely rejoiced at moving to detached housing. Ivan and Leonida Svitlichni moved to one of the newly-built houses in 1960. Their place became an “epicentre of Ukrainian Sixtiers”. In the mid-60s Ivan Dziuba resided here. Viktor Mohylnyi found himself on the opposite side of the spectrum – massive construction of residential buildings expelled him from his house. Chokolivka served as a space of (ab)normal Soviet everyday life for those mentioned above. Daily groceries in gastronom intertwined with systematic ransacks and detentions. The paper lays out the history of Chokolivka and the stories of the Sixtiers within it. The paper further describes the (non)remembrance of Sixtiers layer of rayon’s history.